A educação moral na formação da infância e adolescência desvalida moderna: o caso de Pindobal na Paraíba do século XX (1930-1960) - Nascimento, Gabriel Alves do (2022)
The history of President João Pessoa Professional School (Pindobal) has an aura of undeniable popular mysticism, the belief of an institution that regenerated vagrants, delinquents and strays surrounded the imagination of society in Paraíba throughout the 20th century, producing popular cries such as: “Boy, obey me, otherwise I will send you to Pindobal!”. Pindobal permeates the social imaginary as an institution destined to prison or to regenerate the insane. Between popular belief and true reality there is a gap that this study has attempted to deepen. The methodology used is the Indicative Paradigm (GINZBURG, 1987; 1989; 2007), about 53 (fifty-three) written sources and 49 (forty-nine) iconographic sources were analyzed, which deal with a long period, from 1930 to 1960. Pindobal, as it is popularly known, is an institution that has characteristics of Agricultural Patronage, whose institutional objective is to professionalize, contain, regenerate and educate those considered socially incorrigible – poor and black male children and adolescents. This institution was created in 1930, in the region of Mamanguape, in Paraíba, through Decree 1606, of November 14, 1929, and regulated by Decree 1672, of June 10, 1930. The results obtained through this study characterize Pindobal from four different moments: 1) 1913-1929, the first phase of the institution, managed by the Federal government and founded an Agricultural Center; 2) 1930-1940, with the creation, in 1930, of the President João Pessoa Professional School, managed by the state government; 3) 1941-1949, with Moral Education as the main tool for controlling the inmates of Pindobal through the hands of the Priests of the Sacred Heart of Jesus; and 4) 1950-1960, under the direction of Professor and Social Worker Jandira Pinto, who developed a concept of Assistance Christian Humanist Education. These four distinct moments are present from the social ideology of each period. Pindobal was immersed in psychiatric, pedagogical, legal, religious and agricultural vocational education discourses, culminating in compulsory work in order to moralize, correct and provide them with a useful education. This study approaches the social history of childhood in the 20th century. We hope that this research will serve as a point of arrival or departure for those who wish to investigate the History of Education and the History of Correctional and Agricultural Educational Institutions in Paraíba in the 20th century.